KHITBAH DALAM TRADISI MASYARAKAT DESA BADAS KECAMATAN BADAS KABUPATEN KEDIRI PERSPEKTIF HUKUM ISLAM - Alida Nur Aini; Fachrodin (Jurnal Ilmu Hukum, 2023)
ABSTRACT This study discusses the marriage proposal Tradition in society according to the Perspective of Islamic Law. In accordance with the theory taken by the author from the agreement of the scholars', al-Qur'an, hadith regarding the tradition of exchanging rings which is carried out during the sermon event. The formulation of the problem in this research is How is the khitbah tradition in the Badas community, Badas District?, and What is the perspective of Islamic law regarding the sermon tradition in the community in Badas village, Badas District?. This type of research is case study research. Data collection techniques that the authors use are interviews as well as observation and documentation. The results of the study show that the Badas village community in carrying out the application has the same process as most other traditional customs such as in Islam, usually carrying out several stages including observing to find out the seeds, bebet and weight of the prospective bride and groom, then the introduction stage, after getting to know each other then an event is held application between the two parties by bringing several gifts such as a set of bridesmaids, makeup and skincare tools, toiletries, clothes, jewelry, traditional foods and fruits, several types of cakes or snacks, as well as some money which will later be used to help with expenses future marriage. The sermon tradition in the Badas Village community is not yet in accordance with the guidelines prescribed by Islam. Because they think that exchanging rings is a bond between the groom and the bride. In this tradition there are also some who wear gold rings for their male candidates even though it has been explained that it is forbidden for men to wear gold jewelry. The Badas people think that when they are already in an engagement bond they have certain rights towards their partner so that they get recognition in the community. Keywords : Tradition, marriage proposal, Islamic Law